A strategy paper on Eligardi Enterprises, Incorporated - Pacifico, Luz Mangundayao (Animo Repository, 1999)
1.1 The Company Eligardi Enterprises, Inc. takes pride in being one of the pillars of the Philippine overseas entertainment industry that has curved a niche in the global market. Eli N. Gadiner started a modest venture of deploying live entertainers to US military bases in Vietnam during the height of the Vietnam war in 1967. With a handful of staff, the company succeeded in penetrating the Vietnam market and consequently, the more lucrative market of Japan. Since then, Eligardi has positioned itself among the pioneer Filipino entertainment agencies to enter Japan. With the ever-growing demand for bands, singers, and cultural/variety dancers, more and more hotels, clubs and theater-restaurants opened their doors to Eligardi talents. In response to the government's call to improve the deployment program and upgrade the level of professionalism of the performing artists, EEI's board of directors set up a separate company, CERCAP Philippines (Center for Entertainment Research and Communication for Asia and the Pacific). Cercap functions as an implementing arm for this educational and talent development program. Currently, all Cercap's graduates are EEI's main source of deployable artists. Mr. Gardiner's dream of deploying legitimate and quality artists has been realized. The government through the Philippine Overseas Employment Administration (POEA) has recognized Eligardi's zeal and dedication in the promotion of the entertainment industry and named the company a member of the elite Hall of Fame in 1988. 1.2 Environmental Analysis The essence of formulating corporate strategy is relating a company to its environment. In analyzing the environment of Eligardi Enterprises, Inc., I used Porter's framework of the Five Forces Model, and came up with the following conclusions: (1)Threat of new entrants: Low (2) Rivalry among existing competitors: Intense (3) Pressure from substitute products: Exists (4) Bargaining power of buyers: High (5) Bargaining power of suppliers: High. At first glance , it would seem that the above five forces conspire to reduce the profit potential in the industry, where profit potential is measured in terms of long-run return on invested capital. However, the high industry growth overrides all the other negative forces. The increase in Japan's demand for entertainers despite the currency crisis, plus the shift in demand from low-quality to high-quality entertainers, together ensure that the industry's revenue will continue increasing. Given that the revenue earned is in US dollars, and that the value of the Philippine peso has decreased from its 1997 pre-currency crisis level, the overseas entertainment industry is highly profitable. 1.3 Strategic Map Companies that have similar strategies along given strategic dimensions, such as breath of product line, use of the same kinds of distribution channels, and degree of vertical integration, fall in the same strategic group. For this industry, the strategic dimensions that are most applicable are geographic scope and degree of vertical integration. In this industry, a licensed agency is considered fully integrated if it is affiliated with both a training center and a Japanese promoter. An agency is partially integrated if it is affiliated with either a training center or a Japanese promoter. The strategic groups in the industry are as follows: (1) Group I - Composed of licensed agencies that are affiliated with a training center and a Japanese promoter. These agencies have Japanese owners with Filipino fronts. These firms typically have been existing for less than three years hence, they concentrate on meeting the needs of the Japanese promoter, who operates in one to three regions only. Ten companies make up this group (2) Group II - Composed of licensed agencies that are affiliated with a training center or a Japanese promoter. Most of these firms are the pioneers in the industry which train and develop high-end artists, who are almost always booked by Japanese promoters and/or club-owners who operate in one to three regions. Twelve companies, including EEI, fall in this group (3) Group III - Composed of land-based licensed agencies that deploy entertainers, among other land-based overseas Filipino workers. These agencies cater to very ew Japanese clients and send OPAs to one to three regions only. Five companies, each of which deploys 50 to 100 OPAs a year fall in this group (4) Group IV - Composed of licensed agencies that are affiliated with both a training center and a Japanese promoter. These agencies have Japanese owners with Filipino fronts. These firms have been existing longer than Group I. Hence, they cater to the talent requirements of their Japanese owner, but also book artists to their owner's friend. As such, they are able to deploy OPAs to more regions in Japan. Twelve companies fall in this group (5) Group V - Composed of 10 licensed agencies that are affiliated with a training center or a Japanese promoter. These have been operating for 10 to 15 years. They usually resort to illegal practices in deploying talents, and are able to book them in four to five regions. Company B belongs to this group (6) Group VI - Composed of seven licensed agencies that cater to a handful of Japanese clients and send OPAs from other training centers to four to five regions in Japan. These agency Group II, IV and VII account for more than 50% of the industry's revenues. 1.4 Opportunities and Threats of the Industry The opportunities available to the overseas entertainment industry are as follows: (1) Increase in the Philippine unemployment rate (2) Decline in the value of the Philippine peso (3) Increase in OPAs. The threats facing the industry are as follows: (1) Overstaying Filipinos in Japan (2) Influx of Japanese promoters into the industry (3) Deployment of untrained Guest Relation Officers. 1.5 Strengths and Weaknesses of the Company A strength can be defined as an internal capability of the company. Conversely, a weakness can be defined as the lack of internal capability. Strengths and weaknesses should be evaluated in the light of the opportunities and threats the industry faces. The company's strengths are as follows: (1) Deployment record (2) Absence of long-term debt. The company's weaknesses are as follows: (1) Manual data storage retrieval (2) Idle cash resources (3) Lack of formal management practices. 1.6 Proposed Vision of the Company Eligardi Enterprises, Inc. (EEI) does not have any clearly articulated vision. The proposed vision is as follows: Overseas entertainment is our business. Our vision is to be the Philippines industry leader in giving total client and artist satisfaction through committed, reliable and personalized service. 1.7 Proposed Corporate Objectives The company does not have formally written objectives. The following are the proposed strategies and financial objectives: (1) To increase net income by at least 5% every year until 2002 (2) To move from being one of the top 10 in the industry to being one of the top five in terms of revenue, by 2002 (3) To become fully integrated (4) To expand its geographical scope to five regions in Japan. 1.8 Proposed Corporate Strategies The most appropriate generic strategy for EEI is differentiation. The following are the proposed corporate strategies for EEI: (1) Expand to prefectures in other regions (2) Set up a company based in Kobe that will market Overseas Performing Artists (OPAs) to the different entertainment venues in the nearby prefecture and regions (3) Charge booking fee based on adjusted scheme of the artist's salary (4) Develop management and operational information systems to address the company's information needs. 1.9 Functional Objectives and Strategies Functional Area: (1) Marketing (2) Operations (3) Management Information Systems (4) Human Resource Development. Objectives: (1) Increase revenue from booking fees by 15% by 2002 (2) Achieve full integration in the industry (3) Increase efficiency, increase accuracy of reports, improve customer service and generate of financial reports on a timely basis (4) Achieve greater productivity in the work force. Strategies: (1) a.) Continue its practice of marketing only those artists who have been screened and trained properly and have finished at least 2 years of college education b.) Charge booking fees based on proposed artist's salary scheme c.) Expand its target market to prefecture in other regions (2) a.) Establish an office in the city of Kobe that will act as the company's own promoter in Japan (3) a.) Develop customized application systems b.) Hire a software developer c.) Acquire needed hardware and software (4) a.) Transfer the supervision of the cashier and disbursing officer from the operations manager to the president and general manager b.) Develop a job description for each position c.) Hire a third liaison officer who can scout for potential talents, and a bookkeeper for record keeping d.) Train the president and general manager in the use of the financial management system e.) Train the operation manager, data processor, and secretary in the use of the other application systems f.) Train the bookkeeper in the use of the financial management information system. 1.10 Implementation To implement strategies, the company should make sure that the other aspects of the organization are also considered. The framework used for strategy implementations is the Seven - S model. (1) Strategy (2) Structure (3) Systems (4) Skills (5) Staff (6) Style (7) Super Ordinate Goals/Shared Values."